Isaac le Long’s German Version of Grevenbroek’s Khoekhoe Glossaries as Published by Juncker in 1710 - Besten, Hans den (Department of Dutch and South African Studies, Faculty of English, 2010)
Over the years researchers have hit upon two Khoekhoe documents in the Herrnhut Archives of the Brüder-Unität. These documents, which I will call Hh-A and Hh-B, are in essence two pairs of Khoekhoe glossaries with German as the metalanguage. In Hh-A these glossaries are presented consecutively and in Hh-B in a parallel fashion. Document Hh-B will be discussed only briefly in the present paper, since it derives its data from, and is therefore secondary to Hh-A. It is important to note that Hh-A itself is also a secondary product, since it is based upon two Khoekhoe glossaries compiled by the Cape Colonial intellectual J.W. de (or: van) Grevenbroek and published in Juncker (1710). Nevertheless, Hh-A is of some inte rest because it is related to the first Moravian mission to the Khoekhoen (Georg Schmidt, 1737-1744) and because the reshaping of the Juncker glossaries, which yielded Hh-A, was executed by the well-known 18th century Amsterdamian author and translator of French-German descent, Isaac le Long. Le Long replaced the Latin column that Juncker had added to the Khoekhoe glossaries with a translation of his own, in German. Hence a comparison of both translations is called for, which means that not only le Long’s manuscript Hh-A will be reproduced in this article, but also Juncker’s edition of the pertinent glossaries. These text editions can be found in the Appendices A and B, which are preceded by six sections of running text. After an introductory section, section 2 will discuss the textual network Hh-A is part of, as well as its historical context. Section 3 will discuss various aspects of the two glossaries as can be found in Juncker (1710), such as the structure and the contents of the two glossaries, typos and graphemic Germanisms, and the importance of these glossaries for Khoesan and Afrikaans studies. Sections 4 and 5 will discuss Juncker’s Latin, and le Long’s German, column respectively. Flaws in Juncker’s Latin column can be attributed to Juncker’s lack of knowledge of Dutch and partly to the new, bewildering Cape Dutch terminology for the animal kingdom at the Cape. As expected Isaac le Long removed many flaws of Juncker’s edition but for him the new Cape Dutch lexis was also impenetrable. Furthermore, there are formal flaws in his German, which can be interpreted as ‘Dutchisms.’ Section 6, finally, will be a technical introduction of the appendices.
Keywords: Cape Dutch; Cape Khoekhoe; J.W. van Grevenbroek; Isaac le Long; Moravian Brethren; Peter Kolb; Christian Juncker